The Relationship between Islamic Boarding School Leadership and the Professionalism of Ustadz on Performance at the Mambaul Huda Islamic Boarding School in Banyuwangi - Istikomah Istikomah; Babun Suharto; A. Muhtadi Ridwan (Responsive: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyze the relationship between the leadership of Islamic boarding school leaders and the professionalism of ustadz on the performance of ustadz at the Mambaul Huda Krasak Islamic Boarding School, Tegalsari District, Banyuwangi Regency. This study uses a quantitative approach with a correlational method. The study population is all ustadz who teach at the Mambaul Huda Krasak Islamic Boarding School, with the sample determined through a proportional sampling technique. The data collection instrument is a questionnaire compiled based on indicators of Islamic boarding school leadership, ustadz professionalism, and ustadz performance. Data were analyzed using descriptive and inferential statistics. The results of the study indicate that there is a positive and significant relationship between the leadership of Islamic boarding school leaders and the professionalism of ustadz on the performance of ustadz. This finding confirms that effective Islamic boarding school leadership and good ustadz professionalism play an important role in improving ustadz performance.